Quid Pro Quo? What Factors Influence IPO Allocations to Investors? - JENKINSON, TIM; JONES, HOWARD; SUNTHEIM, FELIX (Journal of Finance, 2018)
ABSTRACT Using data from all of the leading international investment banks on 220 initial public offerings (IPOs) raising $160 billion between January 2010 and May 2015, we test the determinants of IPO allocations. We compare investors’ IPO allocations with proxies for their information production during bookbuilding and the broking (and other) revenues they generate for bookrunners. We find evidence consistent with information revelation theories. We also find strong support for the existence of a quid pro quo whereby broking revenues are a significant determinant of investors’ IPO allocations and profits. The quid pro quo remains when we control for unobserved investor characteristics and investor‐bank relationships.